Constitutive activity of the M1-M4 subtypes of muscarinic receptors in transfected CHO cells and of muscarinic receptors in the heart cells revealed by negative antagonists - Jakubík, J; Bacáková, L; el-Fakahany, E E; Tucek, S (FEBS letters, 1995)
We investigated whether muscarinic receptors of the M1-M4 receptor subtypes are constitutively active. We have found that the synthesis of cyclic AMP was enhanced by the muscarinic antagonists atropine and N-methylscopolamine (NMS) in Chinese hamster ovary (CHO) cells stably transfected with human m2 and m4 muscarinic receptor genes and in rat cardiomyocytes expressing the M2 receptor subtype, and that the production of inositol phosphates was inhibited by atropine and NMS in CHO cells stably transfected with human m1 and m3 and with rat m1 muscarinic receptor genes. The muscarinic antagonists quinuclidinyl benzilate and AF-DX 116 had no effect in some cases and acted like atropine and NMS in others. We conclude that the M1-M4 subtypes of muscarinic receptors are constitutively active in the CHO cell lines expressing them and in cardiomyocytes and that atropine and NMS act as negative antagonists on these receptor subtypes by stabilizing them in the inactive conformation.
Keywords: Animals; N-Methylscopolamine; Carbachol; AMP cyklický; křečci praví; chinuklidinylbenzilát; Muscarinic Antagonists; Scopolamine Derivatives; CHO buňky; Atropine; Inositol Phosphates; transfekce; Transfection; Tritium; lidé; karbachol; inositolfosfáty; receptory muskarinové; Pirenzepine; antagonisté muskarinových receptorů; kultivované buňky; Quinuclidinyl Benzilate; Cells, Cultured; Cyclic AMP; N-methylskopolamin; pirenzepin; Receptors, Muscarinic; tritium; krysa rodu Rattus; zvířata; skopolaminové deriváty; atropin; Myocardium; myokard; Rats; Cricetinae; CHO Cells; Humans